Estimating Labor Trafficking among Unauthorized Migrant Workers in San Diego. Issue 1 (May 2014) - Zhang, Sheldon X.; Spiller, Michael W.; Finch, Brian Karl; Qin, Yang
Research on labor trafficking faces many methodological challenges, which make it difficult to provide reliable estimates of the problem. In this research, we applied respondent-driven sampling and unique access to migrant communities in San Diego County, California, to estimate the extent of trafficking violations in one of America's largest Spanish-speaking immigrant destinations. We found that 30 percent of undocumented migrant laborers were victims of labor trafficking, 55 percent were victims of other labor abuses, and about half of these victimization experiences occurred within the past 12 months. The rate of trafficking violations varied markedly across business sectors that typically hire unauthorized migrant workers. Construction and janitorial services had the most reported trafficking violations and labor abuses. Findings in this study also suggest that the illegal status in the country is likely the most significant factor contributing to vulnerability to trafficking violations.